[3-(4-Chlorophenyl)-5-hydroxy-5-phenyl-4,5-dihydro-1H-pyrazol-1-yl](3-pyridyl)methanone - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title compound, C(21)H(16)ClN(3)O(2), the dihedral angles formed by the pyrazole ring with the pyridyl, phenylene and phenyl rings are 6.80 (5), 9.23 (5) and 74.96 (5)°, respectively. The phenyl and phenylene rings are inclined at 80.14 (2)°. Intramolecular O—H⋯O and C—H⋯N hydrogen bonds generate S(6) ring motifs. The crystal packing is strengthened by short intermolecular O—H⋯N, C—H⋯O hydrogen bonds and π–π stacking interactions with centroid–centroid distances of 3.6247 (5)–3.7205 (5) Å, together with intermolecular short O⋯N contacts [2.7682 (11) Å]. Molecules are linked into infinite chains along [100].